2010
DOI: 10.4067/s0718-58392010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Resistance of Transgenic C5 Plum (Prunus domestica L.) against Four Chilean Plum Pox Virus Isolates through Micro-Grafting

Abstract: The transgenic plum (Prunus domestica L.) C5, in which the coat protein (CP) gene of the Plum pox virus (PPV) is inserted, represents a unique example of the use of genetic engineering for fruit crop improvement in Prunus spp. Field trials in Poland, Romania, and Spain have demonstrated resistance of C5 to several D and M strain PPV isolates. In Chile, the quarantine regulations for PPV and for genetically modified (GM) plants require that the testing of C5 for resistance to Chilean PPV isolates be done under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Fortunately, C-5 has generated after the spontaneous rearrangement of PPV coat protein (CP) sequences into an inverted repeat/hairpin configuration during the Agrobacterium -mediated transformation. This resulted in activation of RNA silencing process in regenerated C-5 plant ( Kundu et al, 2008 ), and thus provided long time viral resistance confirmed later by various greenhouse tests and field trials ( Capote et al, 2008 ; Polák et al, 2008 , 2017 ; Wong et al, 2009 ; Scorza et al, 2013 ). Soon it was shown that the introduction of ihpRNA constructs, specifically engineered by joining of the viral fragment as inverted repeats separated by a spacer or an intron, significantly increase the silencing efficiency in host plants ( Khalid et al, 2017 ).…”
Section: Introductionmentioning
confidence: 89%
“…Fortunately, C-5 has generated after the spontaneous rearrangement of PPV coat protein (CP) sequences into an inverted repeat/hairpin configuration during the Agrobacterium -mediated transformation. This resulted in activation of RNA silencing process in regenerated C-5 plant ( Kundu et al, 2008 ), and thus provided long time viral resistance confirmed later by various greenhouse tests and field trials ( Capote et al, 2008 ; Polák et al, 2008 , 2017 ; Wong et al, 2009 ; Scorza et al, 2013 ). Soon it was shown that the introduction of ihpRNA constructs, specifically engineered by joining of the viral fragment as inverted repeats separated by a spacer or an intron, significantly increase the silencing efficiency in host plants ( Khalid et al, 2017 ).…”
Section: Introductionmentioning
confidence: 89%